A prospective study of effect of delayed cord clamping in term babies as well as in preterm babies - Priya, Shaloo; Biswas, Arati; Rani, Saba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Delayed cord clamping (DCC) is lengthening the time between delivery of newborn and the clamping of their umbilical cord. It is usually performed 25 seconds to 5 minutes after birth, which increases the newborn’s iron storage, vital for healthy brain development. Methods: This prospective observational study was conducted on 100 late preterm and term newborns delivered in the obstetrics and gynaecology department of Calcutta national medical college and hospital, Kolkata over a period of one and half years (March 2019 to August 2020). The umbilical cord was clamped between 60 to 90 seconds after birth of baby. Babies’ weight measurement and blood investigations (Haemoglobin (Hb) level, total serum bilirubin (TSB) and serum ferritin) were performed at birth, after 24 hours of birth and at 6 weeks of age. Results: In this study after DCC, there is significant increase in Serum Ferritin levels after 24 hours and 6 weeks as compared to the birth values. As far as the values of TSB and hemoglobin is concerned, the values first showed increment after 24 hours and then decreased at 6 weeks, which is statistically significant (p=0.001). Birth weight which first decreased after 24 hours, increased at 6 weeks. None of the babies needed blood transfusion during the study period. Out of 100 cases, 9 were admitted in NICU and required phototherapy which was not directly associated with umbilical cord clamping time or bilirubin values at birth. Conclusions: Based on the results of this study, we conclude that newborns with DCC had statistically significant higher levels of Hb and ferritin after birth. This may ensure better iron status throughout infancy along with reduced need of blood transfusion and its related adversities. Delaying cord clamping seems to be beneficial in late preterm and term neonates without causing additional morbidities in the first 6 weeks of life.